Ten priority questions for increasing the consistency and success in hatchery production of the European flat oyster for habitat restoration - zu Ermgassen, Philine S.E.; Albentosa, Marina; Bakker, Nienke; Blanco, Ainhoa; Bonačić, Kruno; Carboni, Stefano; Brundu, Gianni; Colsoul, Bérenger; Araujo Piñeiro, Nicolás; da Costa, Fiz; Dubbeldam, Marco; Fabra, Monica; et al. (Aquatic living resources (Montrouge), 2023)
The European flat oyster, Ostrea edulis , once formed extensive reef habitats throughout European seas and estuaries. These reefs are now largely functionally extinct, yet interest and support for their restoration is rapidly growing. A major bottleneck to scaling up oyster reef restoration is the lack of available oysters to supply the growing demand. This study aimed to identify the ten questions which, if answered, would increase the consistency and success in hatchery production of O. edulis for habitat restoration. Candidate questions were submitted by representatives from twelve commercial and research hatcheries across Europe. The list of 98 candidate questions were collaboratively discussed by experts from nine research hatcheries across eight countries in Europe, to identify the top ten questions via an iterative and open process. Questions were grouped into the following themes: conditioning and feeding, larval rearing, disease and water quality, hatchery protocol, genetics, and hatchery management. There were several overarching topics spanning these themes, including diet optimisation, maximising the effective population size, and developing the technical skillbase in order to increase hatchery production to meet the projected increase in demand for oyster seed for habitat restoration efforts. We anticipate this list will provide a starting point for collaborative research efforts across Europe, as well as assisting policy makers and funders in identifying key knowledge gaps.